2017
DOI: 10.3390/ijms18020294
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Biomarkers in Urine of Cushing’s Syndrome Patients

Abstract: Cushing’s syndrome (CS) is a disease which results from excessive levels of cortisol in the human body. The disorder is associated with various signs and symptoms which are also common for the general population not suffering from compound hypersecretion. Thus, more sensitive and selective methods are required for the diagnosis of CS. This follow-up study was conducted to determine which steroid metabolites could serve as potential indicators of CS and possible subclinical hypercortisolism in patients diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 46 publications
0
25
2
Order By: Relevance
“…Authors reported increased urinary concentrations of androsterone, etiocholanolone, pregnenetriol, tetrahydrocorticosterone, tetrahydrocortisol, allo‐tetrahydrocortisol, and α‐cortol, as well as decreased concentrations of tetrahydrocortisone in patients with CS ( Table ). When urine steroid profiling of patients with NFAT was compared with healthy controls, authors observed similar differences, postulating that at least a subgroup of patients with adrenal incidentalomas may have had underlying MACS that was not detected by currently available biochemical tests . Surprisingly, authors have not demonstrated androgen decrease as expected in ACTH‐independent cortisol excess, possibly due to imperfect age and sex matching or due to inclusion of two patients with pituitary CS in analysis.…”
Section: Approach To Management In Patients With Macsmentioning
confidence: 82%
See 1 more Smart Citation
“…Authors reported increased urinary concentrations of androsterone, etiocholanolone, pregnenetriol, tetrahydrocorticosterone, tetrahydrocortisol, allo‐tetrahydrocortisol, and α‐cortol, as well as decreased concentrations of tetrahydrocortisone in patients with CS ( Table ). When urine steroid profiling of patients with NFAT was compared with healthy controls, authors observed similar differences, postulating that at least a subgroup of patients with adrenal incidentalomas may have had underlying MACS that was not detected by currently available biochemical tests . Surprisingly, authors have not demonstrated androgen decrease as expected in ACTH‐independent cortisol excess, possibly due to imperfect age and sex matching or due to inclusion of two patients with pituitary CS in analysis.…”
Section: Approach To Management In Patients With Macsmentioning
confidence: 82%
“…Urine profiling of 19 steroids by GC‐MS was reported in 25 patients with adrenal incidentalomas, 16 patients with overt CS (14 adrenal and 2 pituitary CS), and 37 healthy controls . Authors reported increased urinary concentrations of androsterone, etiocholanolone, pregnenetriol, tetrahydrocorticosterone, tetrahydrocortisol, allo‐tetrahydrocortisol, and α‐cortol, as well as decreased concentrations of tetrahydrocortisone in patients with CS ( Table ).…”
Section: Approach To Management In Patients With Macsmentioning
confidence: 99%
“…Kotłowska et al [ 76 ], studying Cushing disease, reported increased urinary levels of cortisol metabolites, androgens, and pregnanetriol and decreased level of tetrahydrocortisone. These data were similar to those reported in the 1990s [ 77 ]; however, they used heat maps to illustrate their data.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that anabolic hormone disorders cause several pathologies in humans including unnatural metabolic profiles 143 . Metabolomics has been proposed as a tool to diagnose hormonal deficiencies, 144 or to track metabolic changes in hormonally supplemented patients, 42,145,146 to evaluate the effect of the treatment. Starting from information on the general working principle of each hormone and gathering information from studies on hormonally treated patients, it is possible to speculate on the expected dose‐dependent effect on human metabolism of each class of hormones.…”
Section: A Metabolomics Approach For Hormone Screening?mentioning
confidence: 99%